Genetic polymorphisms affecting antioxidant enzymes are present in tympanosclerosis patients - Akyigit, A.; Yalcin, S.; Etem, E. O.; Kaygusuz, I.; Karlidag, T.; Keles, E.; Tektemur, A. (Cambridge Univ Press, 2016)
Background: This study investigated genetic polymorphisms affecting the inducible nitric oxide synthase, superoxide dismutase and catalase enzymes in chronic otitis media patients with and without tympanosclerosis, and the role of genetic susceptibility in the disease aetiology. Methods: A total of 162 patients who underwent surgery for chronic otitis media were divided into two study groups: a tympanosclerosis group and a chronic otitis media group. A third, the control, group comprised 188 healthy volunteers. Venous blood samples were evaluated using reverse transcriptase polymerase chain reaction. Results: There was a significant difference in GG genotype distribution of the -277A>G polymorphism in the NOS2 gene between the tympanosclerosis and control groups (p < 0.05). However, there were no significant between-group differences in the CC genotype distribution of the p.Ala16Val (C>T) polymorphism in the SOD2 gene (p > 0.05). There were significant differences in the TT genotype distribution of the -21A>T polymorphism in the CAT gene between the tympanosclerosis and control groups, and between the chronic otitis media and control groups (p < 0.05). Conclusion: These results suggest that genetic predisposition may play a role in the aetiopathogenesis of tympanosclerosis.
Keywords: Tympanosclerosis; Nitric Oxide Synthase Type II; Superoxide Dismutase; Catalase; Polymorphism; Genetic